Digital natives: where is the evidence? - Helsper, E; Eynon, R (Routledge, 2010)
Generational differences are seen as the cause of wide shifts in our ability to engage with technologies and the concept of the digital native has gained popularity in certain areas of policy and practice. This paper provides evidence, through the analysis of a nationally representative survey in the UK, that generation is only one of the predictors of advanced interaction with the Internet. Breadth of use, experience, gender and educational levels are also important, indeed some cases more important than generational differences, in explaining the extent to which people can be defined as a digital native. The evidence provided suggests that it is possible for adults to become digital natives, especially in the area of learning, by acquiring skills and experience in interacting with information and communication technologies. This paper argues that we often erroneously presume a gap between educators and students and that if such a gap does exist, it is definitely possible to close it.